What makes Indonesian Eastern students struggle on academic performance at urban college: A grounded theory - Musthofiyah, Uning; Isnainiyah, Lilik (D3 English Program Universitas Merdeka Malang, 2020)
A Grounded Theory was employed to design a theoretical model for explaining a phenomenon of low academic performance among a minority group at Urban college, henceforth referring to as Indonesian Eastern Students.Â Â 15 college students were purposively selected to take a semi-structured interview focus group about perspectives, experiences and insights that might hinder minority students in academic performance, putting a limelight on how they constructed self-identity through social interaction on and off campus. Through social justice perspective, this research finding offered theoretical framework to improve student performance in academics, to reduce the gap of educational disparity and foster inclusive education in Indonesia.Â DOI: 10.26905/enjourme.v4i2.4311